A transitividade e a relevância discursiva em notícias de feminicídio - Neto, Alfredo Evangelista dos Santos (2020)
The phenomenon of transitivity has been a widely discussed topic among language researchers, as there is no uniform classification among grammarians that allows to define precisely the limits of the verb's action in the sentence. This study aims to unders